Study on the Effect of Recycled Brass-Filled Epoxy Mould Inserts for Rapid Tooling - Norhafisha Binti Syed Mohd; Shayfull Zamree Abd Rahim; Mohd Hazwan Mohd Hanid; Allan Rennie; Abdellah El-hadj Abdellah; Nor Atikah Binti Zakaria (Archives of Metallurgy and Materials)
Rapid Tooling able to produce complex prototypes directly from three-dimensional CAD software using materials such as polymer, wax, and paper, but it is typically used for low-volume production. The current technology uses epoxy filled with metal fillers such as aluminum or copper to enhance the mechanical properties of rapid tooling molds. This study aims to investigate the effect of using recycled brass filler mixed with epoxy resin as mold inserts for Rapid Tooling in injection molding applications. An optimal ratio of brass filler particles will be evaluated to determine the best physical and thermal properties for the mold inserts. Significantly, this study will encourage the use of recycled materials such as metal waste from machining to offer great help in environmental sustainability.